PENGARUH LAMA PENGERINGAN BETON SERAT PANDAN PUNDAK DURI (PANDANUS TECTORIUS) TERHADAP KUAT TARIK BELAH BETON - hadi, faizal; Gunawan, Agustin (Universitas Bengkulu, 2019)
Concrete is a material that have the strength to compression, but it is weak against tensile strength. The weakness of the tensile strength of concrete can be minimized by adding pandanus tectorius fiber. This study was aimed to determine the effect of adding pandanus tectorius fiber to split- tensile strength of concrete and percentage of the fiber in concrete that shows the highest split- tensile strength. The specimens used in this study is cylindrical with dimensions of 30 cm in height and 15 cm in diameter (SNI 03-4810-1998). Total of specimens is 32 that consist of 8 normal concretes and 24 variation concretes. An addition of pandanus tectorius fiber with the variation of 0,25%, 0,5%, and 0,75% was based on volume of the specimen. The mix design of concrete used water-cement ratio of 0.5 and slump of 60-100 mm. The splittensile strength of concrete was tested at 7 days and 14 days of dryng after immersing for 27 days. The result of split-tensile strength test of concrete with a variation of pandanus tectorius fiber showed a decreasing. The decreasing of split-tensile strength of concrete at 41 days was smaller than at 34 days to normal concrete. The highest decreasing percentage of split-tensile strength of variation concrete to normal concrete was respectively 9,249% (variation 0,25 tested at 41 days) and 14,518% (variation 0,75% tested at 34 days) .